(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers the possibilities of systematic analysis in overcoming the problems of improving the integrity of the system "The role and significance of the activities of Amir Temur and Temurids in the history of the Republic of Uzbekistan and the world." A working model was selected to conduct the systematic analysis. Criteria for improving the integrity of the system under analysis have been developed.